Carrier trapping and confinement in Ge nanocrystals surrounded by Ge3N4 - Park, Y; Chan, C; Reid, B; Nuttall, L; Taylor, R; Lee, N; Lee, Y (Nature Publishing Group, 2016)
We investigated the optical properties of Ge nanocrystals surrounded by Ge3N4. The broad emission ranging from infrared to blue is due to the dependence on the crystal size and preparation methods. Here, we report high resolution Photoluminescence (PL) attributed to emission from individual Ge nanocrystals (nc-Ge) spatially resolved using micro-photoluminescence and detailed using temperature and power-dependent photoluminescence studies. The measured peaks are shown to behave with excitonic characteristics and we argue that the spread of the nc-Ge peaks in the PL spectrum is due to different confinement energies arising from the variation in size of the nanocrystals.